Unraveling the Wagner Group and Yevgeny Prigozhin: The Enigma of Prigozhin's 'March of Justice - Gurbanov, Yunis (European Scientific Journal, ESJ, 2023)
The text discusses significant recent developments in Russia's political landscape, notably the Prigozhin insurgency, which challenged the "perception of stability" under President Putin. The author highlights the potential scenarios for the country's future. When examining the attempted coup in Russia, it's crucial to highlight Vladimir Putin's vulnerability, evident in his decision to permit Yevgeny Prigozhin and fellow Wagner PMC leaders to depart unhindered to Belarus. There are enough hypotheses as to why the Wagner PMC, which always protected the interests of the Putin government, revolted against the government. The insurrection was so massive that mercenaries quickly captured Rostov-on-Don during the rebellion, entering the city, including in tanks. During the day, the rebels, with minimal resistance, passed the Voronezh, Lipetsk, and Tula regions, heading to Moscow. The swift conclusion of the rebellion within a day raises numerous uncertainties. The circumstances surrounding it remain puzzling: Prigozhin vanished from the scene, only for Belarusian leader Alexander Lukashenko to emerge. The Ukrainian invasion has serious implications for the Putin government, potentially prompting changes in leadership. The failed coup attempt involving Prigozhin and his departure to Belarus raises questions about Putin's authority and possible arrangements. The text concludes by discussing the impact of a coup on Russia's stability and the potential for multiple coups leading to a tumultuous transition with global implications. It emphasizes the interest in avoiding bloodshed and maintaining stability from both Russian and Western perspectives.